2015
DOI: 10.1111/dom.12513
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity of circadian clocks and consequences for metabolism

Abstract: The increased prevalence of metabolic disorders and obesity in modern society, together with the widespread use of artificial light at night, have led researchers to investigate whether altered patterns of light exposure contribute to metabolic disorders. This article discusses the experimental evidence that perturbed environmental cycles induce rhythm disorders in the circadian system, thus leading to metabolic disorders. This notion is generally supported by animal studies. Distorted environmental cycles, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 145 publications
(221 reference statements)
0
37
0
1
Order By: Relevance
“…Disruption of circadian clocks has long been associated with a range of metabolic disorders including obesity , metabolic syndrome , and type II diabetes . Recently, microbiome dysbiosis has emerged as the mechanistic link connecting metabolic diseases and circadian clock disruption (Fig ).…”
Section: Impact Of Host–microbiome Circadian Crosstalk On Health and mentioning
confidence: 99%
See 1 more Smart Citation
“…Disruption of circadian clocks has long been associated with a range of metabolic disorders including obesity , metabolic syndrome , and type II diabetes . Recently, microbiome dysbiosis has emerged as the mechanistic link connecting metabolic diseases and circadian clock disruption (Fig ).…”
Section: Impact Of Host–microbiome Circadian Crosstalk On Health and mentioning
confidence: 99%
“…Disruption of circadian clocks has long been associated with a range of metabolic disorders including obesity [113][114][115][116][117][118][119][120], metabolic syndrome [114,[121][122][123][124] circadian clock disruption (Fig 2). Indeed, mice with either genetic or environmental impairment of circadian clocks develop a number of metabolic derangements similar to human metabolic syndrome: higher weight, hyperglycemia, insulin resistance, and higher body fat composition, compared to circadian clock-sufficient controls [33,35,129,130].…”
Section: Metabolic Diseasementioning
confidence: 99%
“…Some reinforcing loops are formed by the orphan nuclear receptors from the REV-ERBα-β and RORα-β families, to modulate the rhythmic transcription of Bmal1, Npas and Clock (Guillaumond et al, 2005; Schibler et al, 2015). Recent studies demonstrated that such oscillations in clock genes expression paralleled critical events of chromatin remodeling (Coomans et al, 2015; Masri et al, 2015). …”
Section: Hypothalamic Integration Of Circadian Informationmentioning
confidence: 99%
“…It is widely accepted that daily endocrine rhythms are outputs of the circadian system, but recent reports suggest that several hormones may act as inputs in the timing signalization of hypothalamic and peripheral clocks (Challet, 2015; Coomans et al, 2015). …”
Section: Hypothalamic Integration Of Circadian Informationmentioning
confidence: 99%
“…One possibility is that the age-related changes in body composition may be due to changes in the homeostatic response to hormonal and signaling factors that regulate body weight and adiposity [22]. Additionally, other factors such as changes in circadian rhythm, which are commonly seen with aging and aging-related dementia, may impact systemic metabolism that lead to age-related alterations in body weight and body composition [23,24]. …”
Section: Body Weight/adiposity In Normal Aging and Age-related Dementiamentioning
confidence: 99%